2003
DOI: 10.1093/nar/gkg108
|View full text |Cite
|
Sign up to set email alerts
|

TRANSFAC(R): transcriptional regulation, from patterns to profiles

Abstract: The TRANSFAC database on eukaryotic transcriptional regulation, comprising data on transcription factors, their target genes and regulatory binding sites, has been extended and further developed, both in number of entries and in the scope and structure of the collected data. Structured fields for expression patterns have been introduced for transcription factors from human and mouse, using the CYTOMER database on anatomical structures and developmental stages. The functionality of Match, a tool for matrix-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
1,605
2
6

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,854 publications
(1,650 citation statements)
references
References 20 publications
20
1,605
2
6
Order By: Relevance
“…This scanning successfully identified 10 bona fide in vivo ARBSs with a Po1e-5. Notably, all of the 10 ARBSs included ARE sequences as determined by the sequence analysis utilities based on TRANSFAC or JASPER transcription factor-binding profiles (Matys et al, 2003;Sandelin et al, 2004), and ChIP-PCR validation confirmed that those ARBSs had abilities to recruit AR ligand dependently. Our ChIPchip approach is a powerful high-throughput method that can be applied to the whole genome-wide screen of ARBSs.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This scanning successfully identified 10 bona fide in vivo ARBSs with a Po1e-5. Notably, all of the 10 ARBSs included ARE sequences as determined by the sequence analysis utilities based on TRANSFAC or JASPER transcription factor-binding profiles (Matys et al, 2003;Sandelin et al, 2004), and ChIP-PCR validation confirmed that those ARBSs had abilities to recruit AR ligand dependently. Our ChIPchip approach is a powerful high-throughput method that can be applied to the whole genome-wide screen of ARBSs.…”
Section: Discussionmentioning
confidence: 85%
“…Using a weighted matrix-based finder TRANSFAC (Matys et al, 2003) with the matrix conservation >75% or a sequence analysis utility of JASPER with the relative profile score threshold >70% (Sandelin et al, 2004), we identified canonical ARE sequences in all of the ARBSs (Table 2).…”
Section: Screen Of Arbss On Encode Dna Microarraymentioning
confidence: 99%
See 1 more Smart Citation
“…The cluster of Myc-binding sites contains three canonical (CACGTG or CATGTG) and one noncanonical (CACATG) sequence motives (Blackwell et al, 1993). The C/EBPa site perfectly conforms to the consensus TTNNNNAA and is detected with a high score by the AliBaba and TFSEARCH algorithms (Grabe, 2002;Matys et al, 2003). Sequence comparison of the promoter regions of WS5 and of the presumed chicken ortholog Mmp115 (Gallus gallus linkage group E22C19W28 genomic contig, NW_100947.1, nt 3231-2972) revealed conservation of the putative Myc-and C/EBPa-binding sites (Figure 2d).…”
Section: Specific Expression Of Ws5 In Myc-transformed Avian Fibroblastsmentioning
confidence: 99%
“…The presence of potential transcription factor binding sites was determined using MatInspector professional in combination with the TRANSFAC database. 17 With classical TATA and CCAAT boxes being absent, the promoter 'backbone' is mainly built by a series of SP-1 sites. From the variety of potential transcription factor binding sites (see Figure 7a), p53 and E2F-1 have been found to be functional and lead to increased APAF1 expression.…”
Section: Analysis Of the Common Apaf1/ikip Promoter Reveals Regulatiomentioning
confidence: 99%